Endgame Polio: Role of Novel Oral Polio Vaccine Type 2 - Sumitha Nayak (Pediatric Infectious Disease)
Polio eradication efforts have seen major advances since 1988 when the thrust for eradication was initiated on a global level. The endgame polio strategy, as announced by the World Health Organization (WHO), is a program from 2019 to 2023 that attempts at the four-point target of eradication, integration, containment, and certification of polio that has ravaged the world across centuries. According to the latest available data, Pakistan has reported 11 cases of wild poliovirus type 1 (WPV1) in 2022, while Afghanistan reported four cases since the start of 2022. Mozambique reported one case of WPV1 in March 2022, while Malawi had one reported case in November 2021. Circulating vaccine-derived poliovirus (cVDPV) types 1, 2, and 3 have been reported from various parts of the globe, especially from the African continent. Active methods are needed to combat and mitigate the spread of PV, especially in the vulnerable and under-immunized regions of the world. The WHO has authorized the use of a novel oral polio vaccine (nOPV), which has been found to be more stable and not revert to neurovirulence when used in the community. These candidates' vaccine is being used in cases of outbreaks of cVDPV, with good results.